Agile Project Management: Creating Innovative Products - Highsmith, Jim (Addison Wesley, 2009)
Best practices for managing projects in agile environments—now updated with new techniques for larger projectsToday, the pace of project man agement moves faster. Project management needs to become more flexible and far more responsive to customers. Using Agile Project Management (APM), project managers can achieve all these goals without compromisi ng value, quality, or business discipline. In Agile Project Management , Second Edition, renowned agile pioneer Jim Highsmith thoroughly upda tes his classic guide to APM, extending and refining it to support eve n the largest projects and organizations.  Writing for project leaders , managers, and executives at all levels, Highsmith integrates the bes t project management, product management, and software development pra ctices into an overall framework designed to support unprecedented spe ed and mobility. The many topics added in this new edition include inc orporating agile values, scaling agile projects, release planning, por tfolio governance, and enhancing organizational agility. Project and b usiness leaders will especially appreciate Highsmith’s new coverage of promoting agility through performance measurements based on value, qu ality, and constraints. This edition’s coverage includes: Understandin g the agile revolution’s impact on product development Recognizing whe n agile methods will work in project management, and when they won’t S etting realistic business objectives for Agile Project Management Prom oting agile values and principles across the organizationUtilizing a p roven Agile Enterprise Framework that encompasses governance, project and iteration management, and technical practicesOptimizing all five s tages of the agile project: Envision, Speculate, Explore, Adapt, and C loseOrganizational and product-related processes for scaling agile to the largest projects and teamsAgile project governance solutions for e xecutives and management  The “Agile Triangle”: measuring performance in ways that encourage agility instead of discouraging itThe changing role of the agile project leader